Evaluation of Genetic Diversity of Sichuan Common Wheat Landraces in China by SSR Markers - Wei LI (Journal of Integrative Agriculture, 2013)
Genetic diversity of 62 Sichuan wheat landraces accessions of China was investigated by agronomic traits and SSR markers. The landrace population showed the characters of higher tiller capability and more kernels/spike, especially tiller no./plant of six accessions was over 40 and kernels/spike of three accessions was more than 70. A total of 547 alleles in 124 polymorphic loci were detected with an average of 4.76 alleles per locus by 114 SSR markers. Parameters analysis indicated that the genetic diversity ranked as genome A > genome B > genome D, and the homoeologous groups ranked as 5>4>3>1>2>7>6 based on genetic richness (Ri). Furthermore, chromosomes 2A, 1B and 3D had more diversity than that of chromosomes 4A, 7A and 6B. The variation of SSR loci on chromosomes 1B, 2A, 2D, 3B, and 4B implied that, in the past, different selective pressures might have acted on different chromosome regions of these landraces. Our results suggested that Sichuan common wheat landraces is a useful genetic resource for genetic research and wheat improvement.